STUDY ON THE EFFECT OF PRESSURE ON WAVE VELOCITY MEASUREMENT OF ROCK SAMPLES USING SEISMIC ROCK PHYSICS - KASMANTO (NIM : 10211037), AHMAD
The study of effects of pore pressure in samples of core rocks it is very important in industry oil and natural gas , both in the exploration and drilling. Measurement with seiscoreTM in laboratory sample of core rock given the pore pressure and overburden pressure so obtained value P-wave velocity ( Vp ) and S-wave velocity ( Vs ). Sample rock core which is rocks shale, sandstone, and carbonate. Graphics P-wave velocity (Vp ), S-wave velocity ( Vs ), and modulus of elastics faced by effective pressure. The pressures can happen because of the trustfault, normal fault, strike-slip fault, and because of the effect bouyancy. P-wave velocity (Vp) increases logarithmically when exerted pressure on the rock overburden clay (shale) and sandstone (sandstone). P-wave velocity to the carbonate rock is not significantly increased. S-wave velocity (Vs) increases in value logarithmically when exerted pressure on the rock overburden clay (shale) and sandstone (sandstone). S-wave velocity in carbonate rocks increased insignificantly. This is caused by the pores in carbonate rocks are very small and solid.